Small genomes and the difficulty to define minimal translation and metabolic machineries - Gil, Rosario; Peretó, Juli (Frontiers in Ecology and Evolution, 2015)
The notion of minimal life has sparked the interest of scientists in different fields, ranging from the origin-of-life research to biotechnology-oriented synthetic biology. Whether the interest is focused on the emergence of protocells out of prebiotic systems or the design of a cell chassis ready to incorporate new devices and functions, proposing minimal combinations of genes for life is not a trivial task. Using comparative genomics and biochemistry of endosymbionts (i.e., intracellular mutualistic symbionts) and intracellular parasites, a decade ago we proposed the core of a minimal gene set for a simple heterotrophic cell adapted to a chemically complex environment. In this work, we discuss the state-of-the-art of the definition of the minimal genome, based on our current knowledge about bacteria with naturally reduced genomes, including both endosymbionts and free-living cells. Any proposed minimal genome would be composed by a set of protein-coding and RNA genes involved in the flux of genetic information (from DNA to functional proteins) and a group of protein-coding sequences embodying a minimalist, stoichiometrically consistent metabolic network. Although the informational portion of the minimal genome is considered quasi-universal, previous proposals have not addressed the need of tRNA post-transcriptional modifications in order to perform their function. For this reason, we have focused on the essentiality of some enzymes involved in such modifications, in order to refine the set of informational genes. As for the metabolic aspect, an obvious difficulty is that there is no one minimal gene set for life but many, depending on the environment. Among cells with reduced genomes, we find a continuum of metabolic modes, from organic matter-dependent heterotrophy to the minimally demanding autotrophy. Both best-known cases of cells with small genomes, the endosymbionts and the ultra-small free-living bacteria, speak in favor of metabolic sharing as a strong force in genome reductive evolution. A hierarchy of minimal cells supported by different metabolic networks with a complexity inversely correlated with the chemical complexity of the environment can be postulated.